The International Pulsar Timing Array: second data release. Issue 4 (12th October 2019) - Perera, B B P; DeCesar, M E; Demorest, P B; Kerr, M; Lentati, L; Nice, D J; Osłowski, S; Ransom, S M; Keith, M J; Arzoumanian, Z; Bailes, M; Baker, P T; et al.
ABSTRACT: In this paper, we describe the International Pulsar Timing Array second data release, which includes recent pulsar timing data obtained by three regional consortia: the European Pulsar Timing Array, the North American Nanohertz Observatory for Gravitational Waves, and the Parkes Pulsar Timing Array. We analyse and where possible combine high-precision timing data for 65 millisecond pulsars which are regularly observed by these groups. A basic noise analysis, including the processes which are both correlated and uncorrelated in time, provides noise models and timing ephemerides for the pulsars. We find that the timing precisions of pulsars are generally improved compared to the previous data release, mainly due to the addition of new data in the combination. The main purpose of this work is to create the most up-to-date IPTA data release. These data are publicly available for searches for low-frequency gravitational waves and other pulsar science.